(untitled) (Journal of Nepal Geological Society, 2004)
Three of the five thrust fault systems defining the boundaries of four lithotectonic terranes of the Himalaya and involved in controversies related to their positions and nomenclature, are the objects of discussion in this paper. Youngest of the five terrane-defining faults, the Himalayan Frontal Fault (HFF) is a series of reverse faults that demarcates the boundary of the Siwalik front of the Himalayan province with the alluvial expanse of the Indo-Gangetic Plains. Over large tracts, it is either concealed under younger sediments or has as yet not reached the ground surface and is therefore a blind fault. The nature of this frontal fault varies along its length. Where the hidden ridges of the Indo-Gangetic basement impinge the Himalaya, the mountain front is ruptured and the HFF is repeatedly reactivated. In the sectors intervening these ridges, it is not expressed on the surface, but the ground of the adjoining Indo-Gangetic Plain is sinking, the rivers are shifting their courses and large tracts of land are waterlogged and characterized by The Vaikrita Thrust is the plane that marks pronounced metamorphic break and abrupt change in style and orientation of structures within the succession of crystalline rocks that build the bulk of the snowy ranges in the Kumaun Himalaya. Not only is there a jump of pressure of the order of 4 kb and a temperature rise of >200 oC, but also is there a conspicuous change of neodymium isotope value across the tectonic plane that separates the low-grade metarnorphics in the lower part from the high-grade metamorphic rocks of the upper part of the Great Himalayan succession. The Vaikrita Thrust is therefore recognised as the Main Central Thrust (MCT). While the basal low-grade metamorphic assemblage comprises 1900±100 Ma old highly tectonised porphyritic granite characterised by low initial strontium isotope ratio, the upper high -grade metamorphic group is intruded by 20±1 Ma old anatectic granites characterised by garnet, kyanite, sillimanite and cordierite, and a high but variable value of strontium isotope ratio. Moreover, the anatectic Lower Miocene granites are singularly absent in the succession of the Lesser Himalayan nappes. Probably it is this thrust that has flexed downwards the plane of decoupling and displacement between the under thrusting Indian plate and the overlying Himalayan mass. The terrane-defining fault between the high-grade metamorphics with granitic rocks of the Himadri (i.e., Great Himalaya) and the Tethyan sedimentary pile was recognised as the Malari Thrust Fault in the northern Kumaun Himalaya in the early seventies, as the South Tibetan Detachment System in southern Tibet adjoining north-eastern Nepal in the early eighties and as the Zanskar Shear Zone in north-western Himachal Pradesh in the late eighties. Not only is there an abrupt change in the metamorphic grade across the tectonic plane, but also an attenuation and wholesale elimination of some lithostratigraphic formations of the hanging wall besides the difference in the style of deformation. Exhibiting predominant dip-slip movement in the central sector of the Himalayan arc, the Trans-Himadri Fault (T-HF) was formed as a consequence of the Tethyan sedimentary cover detaching from its rigid foundation of the basement complex that was squeezed up following blocking or slowing down of tectonic movements related to India-Asia convergence. The sedimentary cover lagging behind the thrust up basement complex slid down and toppled over northward and gave rise to back-folds and back-thrusts. In Kashmir, western Himachal Pradesh, central Nepal and north-western Bhutan, in sharp contrast, there was very strong compression, so that the Tethyan sedimentary rocks-along with a slice of the low-grade metamorphic basement in the hanging wall advanced southwards across the Himadri and were emplaced as nappes and klippen south of the Main Central Thrust. The T-HF movement occurred approximately around 20.9 Ma, although the movement had started quite earlier in some places. Quaternary reactivation resulted in river ponding and development of huge lakes such as the Garbyang palaeolake in the Kali valley and the 40,000 year-old Goting palaeolake in the Western Dhauli Valley.